Research on post commencement finance data from South African companies in business rescue - Gordon, Justin (Department of Finance and Tax, 2019)
SA has one of the lowest survival rates of small and medium enterprises (hereafter referred to as “SMEs”), in the world (Edmore, December 2011). Therefore, business rescue is critical in developing SA’s economy, as defined in Section 7(b)(i) of the Companies Act, No.71 of 2008 (“the Act”) which reads: “Promote the development of the South African Economy by encouraging entrepreneurship and enterprise efficieny” The literature on business rescue concludes that post commencement finance is critical to the success of business rescue. However, to date, there has been no research performed on actual data collected from practitioners to answer the question of whether post commencement finance is a predictor of a successful business rescue The findings of this study initially contradict the literature insofar as 56% of business rescues received post commencement finance: however, further investigation showed that only 7% of the total companies in this study received third party financial institutional post commencement finance, with the balance being introduced by shareholders. The main finding of this study was that the introduction of post commencement finance is only a partial predictor of a successful business rescue. Thus, in the case of those companies which received finance, under business rescue, only 57% were successful. Another finding of this study is that the combination that provides the best probability of successful business rescue is when equity, in the business rescue company, is made available after the successful adoption of the business rescue plan.